1994
DOI: 10.1046/j.1525-1438.1994.04030211.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcoma arising in an ovarian mucinous tumor: a case report

Abstract: A case of an ovarian mucinous tumor with a mural nodule is reported. The mucinous tumor was solid and cystic and contained benign, borderline and malignant elements. Within the solid area a nodule representing fibrosarcoma was identified. Mucocoele of the appendix was the other finding in this case. To the best of our knowledge this is the first description of fibrosarcoma arising in an ovarian cystadenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…A review of the literature revealed only five mucinous ovarian tumors with sarcomas, with most of the mural nodules measured > 5 cm in the greatest dimension. In these five cases, they were fibrosarcomatous mural nodule in an ovarian mucinous cystadenoma [ 7 ], fibrosarcoma arising in a mucinous cystadenocarcinoma [ 8 ], fibrosarcoma associated with a mucinous cystadenoma [ 9 ], undifferentiated sarcoma in a mucinous cystadenocarcinoma [ 9 ], and rhabdomyosarcoma coexistent with ovarian mucinous cystadenocarcinoma [ 10 ], respectively. Ovarian mucinous borderline tumor accompanied by LGESS with myxoid change in our case was rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed only five mucinous ovarian tumors with sarcomas, with most of the mural nodules measured > 5 cm in the greatest dimension. In these five cases, they were fibrosarcomatous mural nodule in an ovarian mucinous cystadenoma [ 7 ], fibrosarcoma arising in a mucinous cystadenocarcinoma [ 8 ], fibrosarcoma associated with a mucinous cystadenoma [ 9 ], undifferentiated sarcoma in a mucinous cystadenocarcinoma [ 9 ], and rhabdomyosarcoma coexistent with ovarian mucinous cystadenocarcinoma [ 10 ], respectively. Ovarian mucinous borderline tumor accompanied by LGESS with myxoid change in our case was rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the cell line was established from a sarcomatous mural nodule of a borderline mucinous cystadenoma. In rare instances, cystic ovarian mucinous tumors contain spindle cell mural nodules (SCMN) (12–31) . These SCMN have been reported to include sarcomas (12,18–21,27) , reactive sarcoma‐like nodules (13,17,24,29) , anaplastic carcinomas (14–18,23,25,26,30,31) , combined sarcoma‐like nodules and carcinomas (17,22) , and leiomyomas (20,23,28) .…”
Section: Discussionmentioning
confidence: 99%
“…In rare instances, cystic ovarian mucinous tumors contain spindle cell mural nodules (SCMN) (12231) . These SCMN have been reported to include sarcomas (12,18221,27) , reactive sarcoma-like nodules (13,17,24,29) , anaplastic carcinomas (14218,23,25,26,30,31) , combined sarcoma-like nodules and carcinomas (17,22) , and leiomyomas (20,23,28) . Thus, the prognosis of the ovarian tumor can be dramatically modified by the presence of this nodule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, fibrosarcoma is associated with Mafucci's syndrome 7 or the naevoid basal cell carcinoma syndrome 8 . Fibrosarcomas have also been described within an ovarian mucinous neoplasm 9,10 . In the present case, although there was no marked nuclear pleomorphism or evidence of tumour cell necrosis, a diagnosis of malignancy was made because of the high mitotic rate.…”
Section: Discussionmentioning
confidence: 99%